Werktreue Ideology in Clara Schumann’s and Franz Liszt’s Piano Transcriptions (Journal of the Society for Musicology in Ireland, 2023)
The piano transcriptions of Clara Schumann (hereafter ‘Schumann’) and Franz Liszt capture the tensions surrounding the concepts of interiority and virtuosity in nineteenth-century Germany. The two composers’ transcriptions of Robert Schumann’s ‘Widmung’ could not be more different: one draws upon the faculty of the mind with its ‘spirit and depth’, the other prizes ‘spirit over the letter’ with its bodily engagement. Nonetheless, there is an important meeting point to be found between these two differing approaches in Liszt’s transcription of three Lieder by Schumann.In this article, I juxtapose Schumann and Liszt to demonstrate how their ideological differences concerning Werktreue, or ‘fidelity to the score’, problematize received notions of virtuosity and interiority. Alexander Stefaniak’s notion of elevated virtuosity, in which virtuosity can be legitimized with interiority for its attendant spirit and depth, offers a productive starting point to understanding Schumann’s and Liszt’s individual manner of transcription. Yet, it does not fully address how ideas of interiority and virtuosity depend upon ideological conceptions of the Work. To probe the interiority-virtuosity divide as it relates to the Work, I refer to the history of improvisation to nuance nineteenth-century attitudes towards virtuosity and to provide a critical discourse around mental and physical engagement with music. The categories of Work and improvisation prove to be much more separated for Schumann than for Liszt– a separation that is bound up with Schumann’s ideal of faithfulness to the Work.